2014
DOI: 10.1016/j.cub.2014.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Stresses at the Cell Surface during Animal Cell Morphogenesis

Abstract: Cell shape is determined by cellular mechanics. Cell deformations in animal cells, such as those required for cell migration, division or epithelial morphogenesis, are largely controlled by changes in mechanical stress and tension at the cell surface. The plasma membrane and the actomyosin cortex control surface mechanics and determine cell surface tension. Tension in the actomyosin cortex primarily arises from myosin-generated stresses and depends strongly on the ultrastructural architecture of the network. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
116
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 148 publications
(209 reference statements)
2
116
0
2
Order By: Relevance
“…Furthermore, reports by Blaser et al (50) showed that a transient increase in myosin activity could lead to increased separation of the acto-myosin cortex from the plasma membrane and the subsequent formation of blebs, while the opposite case of a low myosin II level has been shown to inhibit blebbing and increases filopodia/lamellipodia formation in amoeboid movement (51). However, the exact molecular-scale interactions between myosin II and the plasma membrane-cortex structure remains poorly understood, as summarized by a recent review (52). Several regulatory proteins have been found to function as membrane-to-cortex attachment, such as the ezrin/radixin/moesin proteins and Arp2/3 (53).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reports by Blaser et al (50) showed that a transient increase in myosin activity could lead to increased separation of the acto-myosin cortex from the plasma membrane and the subsequent formation of blebs, while the opposite case of a low myosin II level has been shown to inhibit blebbing and increases filopodia/lamellipodia formation in amoeboid movement (51). However, the exact molecular-scale interactions between myosin II and the plasma membrane-cortex structure remains poorly understood, as summarized by a recent review (52). Several regulatory proteins have been found to function as membrane-to-cortex attachment, such as the ezrin/radixin/moesin proteins and Arp2/3 (53).…”
Section: Discussionmentioning
confidence: 99%
“…This allows for the flexible spatio-temporal regulation of cortical tension to drive cell shape changes and motility. In fact, controlled cortex contractility is a main engine of morphogenesis that is involved in cytokinesis, blebbing locomotion of single cells, or epithelial cell rearrangement through junction remodeling Clark et al, 2014;Sens and Turner, 2006;Lecuit and Lenne, 2007). However, the cortex control mechanism can also be used to rapidly restore the resting tension at the cell surface after surface stretching or shrinking.…”
Section: Cortical Tension a Sustained Contraction Of The Cortical Cymentioning
confidence: 99%
“…Cortical tension is largely but not exclusively based on actomyosin contraction (Pasternak et al, 1989;Tinevez et al, 2009;Stewart et al, 2011) and depends on the density of the cortex, as well as on its structure and composition Clark et al, 2014). Interaction of the cortex with the cell membrane also generates tension, for example, by regulating membrane reservoirs that are required for rapid changes in surface area (Sens and Turner, 2006).…”
Section: Cortical Tension a Sustained Contraction Of The Cortical Cymentioning
confidence: 99%
“…The membrane models mentioned above have by-and-large neglected this active nature of the actin cortex where actin filaments are being continuously polymerized and depolymerized (18-21), in addition to being persistently acted upon by a variety of myosin motors (22-24) that consume ATP and exert contractile stresses on cortical actin filaments, continually remodeling the architecture of the cortex (4, 21, 25). These active processes in turn can generate tangential stresses and currents on the cell surface, which could drive the dynamics and local composition of membrane components at different scales (22,(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…The membrane models mentioned above have by-and-large neglected this active nature of the actin cortex where actin filaments are being continuously polymerized and depolymerized (18-21), in addition to being persistently acted upon by a variety of myosin motors (22-24) that consume ATP and exert contractile stresses on cortical actin filaments, continually remodeling the architecture of the cortex (4, 21, 25). These active processes in turn can generate tangential stresses and currents on the cell surface, which could drive the dynamics and local composition of membrane components at different scales (22,(26)(27)(28)(29).Actin polymerization is proposed to be driven at the membrane by two nucleators, the Arp2/3 complex, which creates a densely branched network, as well as formins that nucleate filaments (18,21,30). A number of myosin motors are also associated with the juxtamembranous actin cortex, of which nonmuscle myosin II is the major component in remodeling the cortex and creating actin flows (4,23,25,26,31,32).…”
mentioning
confidence: 99%